Promosi Penjualan Pakaian Wanita Di Media Sosial Perspektif Hukum Islam - Zalikha, Siti (Ameena Journal, 2023)
The aim of this study is to describe the Islamic law perspective on salam trade and the promotion of women's clothing on social media. This study is a library research study. The analysis revealed that according to Islamic law, salam trade is permissible based on the principles of the religion, but consideration must be given to the commodities that are prohibited by Islam. salam transactions can only be conducted with goods that are permissible in Islamic teachings, thus illegal goods cannot be used as transaction objects. In salam trade, elements that may damage the transaction, such as riba, injustice, fraud, deception, and others, are not allowed. In Islamic law, salam trade is recommended as a fair and just business method. This transaction avoids doubts about the price and quality of the goods, and payment is made in advance to avoid usury and speculation practices. However, in promoting women's clothing on social media, it is important to avoid displaying content that contradicts Islamic values and to adhere to Islamic ethics when using photos and videos to avoid negative impressions.